Combined use of dietary probiotic and acidifier for the production of antibiotic free broiler - Masud, Abdullah Al; Ali, Md Shawkat; Ahammad, Muslah Uddin (Research in Agriculture Livestock and Fisheries, 2016)
The effect of feeding probiotic (Bio-Top; Bacillus subtilis and Bacillus licheniformis), acidifier (Sal-Stop), antibiotic growth promoter (AGP) or probiotic plus acidifier was investigated in commercial broiler. A total of four hundred Cobb 500 day-old straight run chicks were randomly distributed to 5 different dietary groups having 4 replications each. The number of birds in each replication was 20. The five dietary groups were as control (basal diet; BD), BD containing AGP at a level of 20g/100kg, BD containing probiotic at a level of 200g/100kg, BD containing acidifier at a level of 200g/100kg; and BD containing an equal amount of probiotic plus acidifier (200g/100kg). Broilers that received either probiotic, acidifier or a mixture of probiotic and acidifier (1:1) exhibited higher body weight gain, lower feed conversion ratio (FCR) and higher costeffectiveness compared with the broilers fed on control diet (P<0.05). However, feeding of diet containing both probiotic and acidifier resulted in the highest growth rate and net profit in all dietary regimens. Broilers fed on probiotic and acidifier in a mixture had FCR similar to other treatment groups. This study indicated that the diet containing probiotic-acidifier mixture seems to be more cost-effective in promoting growth performance of broilers, as an alternative to the AGP, as compared to the use of probiotic or acidifier alone in the diet Res. Agric., Livest. Fish.3(1): 127-137, April 2016